2016
DOI: 10.1177/1010539516654260
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits of Malaysian Children

Abstract: This article aims to describe the eating habits of Malaysian children using a nationally representative data set from the South East Asian Nutrition Surveys (SEANUTS) in Malaysia. A total of 2797 children aged 2 to 12 years were included in this analysis. Eating habits and dietary intakes of children were assessed using questionnaires. Overall, 56.1% of children consumed 3 main meals every day. Approximately 20% of children snacked 3 times per day, whereas 9.7% ate fast food on a weekly basis. Irregular meal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
(47 reference statements)
2
7
0
Order By: Relevance
“…After the SNP, the children in the IG increased in physical activity at post-intervention and 3-month follow-up, which was consistent with past studies among primary school children [ 58 , 59 ]. In Malaysia, children and adolescents are suggested to perform moderate- or vigorous-intensity physical activity for at least 60 min daily [ 15 ]. The improvement in the physical activity in the SNP may be attributed to the various physical activities run by the trained teachers and the nutrition education, which emphasized the importance of physical activity and a reduction in sedentary activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the SNP, the children in the IG increased in physical activity at post-intervention and 3-month follow-up, which was consistent with past studies among primary school children [ 58 , 59 ]. In Malaysia, children and adolescents are suggested to perform moderate- or vigorous-intensity physical activity for at least 60 min daily [ 15 ]. The improvement in the physical activity in the SNP may be attributed to the various physical activities run by the trained teachers and the nutrition education, which emphasized the importance of physical activity and a reduction in sedentary activity.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has shown that changes in eating behaviors and physical activity pattern are the key factors in the high prevalence of childhood obesity [ 12 ]. Studies have also shown that school-aged children are at risk of poor dietary behaviors (such as skipping breakfast, low intake of fruits and vegetables, and unhealthy snacking) and low physical activity in Malaysia [ 13 , 14 , 15 , 16 ], which may affect their cognitive performance and nutritional status [ 11 , 17 , 18 ]. Based on the Malaysian National Health and Morbidity Survey (2017), only 33.1% of primary school children consume breakfast every day of the week.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these influences were adopted and integrated with local produce and flavors, resulting in significant variation throughout Southeast Asia. In more recent times, the wave of rapid globalization has also brought in a whole new set of flavors through the introduction of fast food into the region [23,[41][42][43].…”
Section: Complexity Of the Southeast Asian Dietmentioning
confidence: 99%
“…Therefore, ethnicity, culture and even religion has a pronounced impact on the choice of foods, types of local ingredients used, structure of meals and patterns of eating behavior. There are further distinctions between urban populations and rural villagers; between the wealthy and the poor; and between the educated and the less educated, and these factors greatly affect access, as well as choice of foods [39,41]. This level of diversity can make it difficult for consumption patterns and behaviors to be accurately defined on a population level [23,41,44].…”
Section: Complexity Of the Southeast Asian Dietmentioning
confidence: 99%
“…Lifelong nutritional patterns are formed during childhood, which can reach at influential stages in their lives [18, 19]. Previous studies reported that Malaysian primary school children are at increased risk of poor dietary behaviours, including breakfast skipping, low fruits and vegetables intakes, unhealthy snacking behaviours and low physical activity [7, 20, 21], which may affect their nutritional status and expose children to malnutrition [22, 23], lower cognitive performance and poor quality of life [24–26]. There is a need to have a holistic nutrition intervention programme that promotes healthy eating and active living for all primary school children, so that they can have a healthy lifestyle, good nutritional status, better cognitive performance and good quality of life.…”
Section: Introductionmentioning
confidence: 99%